Analisis Unsur Intrinsik dan Realitas Sosial Pada Cerpen Hikayat Asam Pedas Karya Azhari Aiyub - rahayu, putri sri; Agustiani, Tanti; Suparman, Fauziah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Social reality is a description of social problems in society that are expressed in a literary work. This social reality is related to the sociology of literature. Literary sociology is the analysis and evaluation of literary works by considering social reality. This research aims to describe the social reality that occurs in the short story Hikayat Asam Pedas by Azhari Aiyub. This research uses descriptive qualitative method. The results of the study found that there are intrinsic elements and social realities that include culture, economy, and suffering in the short story Hikayat Asam Pedas.